ANALISIS PERTUMBUHAN EKONOMI DAN PENETAPAN SEKTOR UNGGGULAN DENGAN MENGGUNAKAN LOCATION QUOTIENT, SHIFT SHARE DAN KLASSEN TYPOLOGY DI MADURA Kabupaten Bangkalan, Kabupaten Sampang, Kabupaten Pamekasan dan Kabupaten Sumenep - mursidi, mursidi; Arief, Sjamsul (Fakultas Ekonomi Universitas 17 Agustus 1945 Surabaya, Indonesia, 2021)
Regional development is a national development device. Regional development is the fruit of innovation and the combination of the region itself to achieve progress and mutual prosperity. The indicator of the achievement of regional development is economic growth that continues to increase. This means that economic growth can continue to increase along with improvements in the economic booster sector. Each region has a different potential, this can be seen from the advantages of each economic sector with a diversity of regional characters that exist and are different. The purpose of this study is to find out the potential sectors that drive growth in East Java and the growth of the localization sector or regional specialist sector. This study uses secondary data obtained from relevant institutions, including Bangkalan, Sampang, Pamekasan, and Sumenep Regency governments, BPS obtained from 2014 and 2018. In analyzing the 17 sectors that will be superior to be focused on the main problem, the Location Quotient test, Shift Share, and typology classifications were used by using an analysis of the four PDRB districts in Madura Island. Based on the results of the study, LQ analysis in Bangkalan, Sampang, Pamekasan, and Sumenep districts contained 5.5, 5, and 5 base sectors. In the Shift Share PR analysis in Bangkalan, Sampang Pamekasan, Sumenep, 5, 6, 7, and 8 sectors encourage growth. While PS 0, 16, 16, and 17 sectors grow relatively fast. DS in 1, 12, 7, and 14 sectors have locational advantages in Madura.